Diseño de un sistema de gestión de compras e inventarios en la empresa STEEL estructuras, planta Latacunga. - Pérez Quevedo, Cristian Paúl (2021)
The present work entitled design of a purchasing and inventory management system in the company Steel Estructuras, Latacunga plant, aims to carry out a purchasing and inventory management system, which will be theoretically supported by analyzing purchasing and inventory management in construction companies, while the current reality of management in the company is established through the gathering of primary information, so that the purchasing and inventory procedures required by the company Steel Estructuras cía can be proposed. Ltda., The methodology used was based on the fact that the project focuses on exploratory research, which is a research method used to study a problem that is not clearly defined, so it is carried out to better understand it, but without provide conclusive results, helping us to focus on the processes that the company maintains in this way is that, the results obtained were that the company Steel Estructuras requires the implementation of the purchasing management system and inventories, in view that the company as Such does not have a correct control over its inventories or purchases, causing it to be oversized and cause losses, in such a way that a management system was developed, which will be made up of 2 modules in which the operation is explicitly explained of the same as well as they will also be divided, with their respective explanation.